Relationship between physical activity during pregnancy and maternal health outcomes: evidence from the MAASTHI cohort study in Bengaluru, India - Ana, Yamuna; van den Brand, Floor A.; van Schayck, Onno C. P.; Babu, Giridhara R. (Frontiers in Sports and Active Living, 2025)
BackgroundSedentary behavior is one of the major modifiable behavioral risk factors for non-communicable diseases. Physical activity (PA) is crucial during pregnancy but pregnant women may become sedentary, leading to adverse health outcomes. Our study aimed to explore the association between social support and PA levels during pregnancy and the relationship between sedentary behavior and adverse pregnancy health outcomes including delivery.MethodsThe study used a validated physical activity questionnaire to assess the physical activity levels of pregnant women. We collected detailed sociodemographic information, pregnancy characteristics, assessed social support. We assessed presence of depressive symptoms and conducted oral glucose tolerance tests, hemoglobin and blood pressure assessments, anthropometric measurements, and collected delivery details. We used linear logistic regression to assess the association between a continuous measure of physical activity level and maternal outcomes and performed multivariable logistic regression analysis to understand the association between sedentary behavior and maternal health outcomes and mode of delivery after adjusting for potential confounders.ResultsWe interviewed 2,424 eligible pregnant women at baseline and 1,317 were considered in the final analysis after excluding those who missed follow-ups. We observed that one unit increase in physical activity level was associated with reduced prenatal depressive symptoms (β = −6.36, p < 0.001), fasting (β = 2.06, p = 0.04), and postprandial blood sugar levels (β = −0.99, p = 0.01), respectively. Pregnant women who had good social support tended to engage in higher levels of activity. In addition, women who engaged in sedentary behavior during pregnancy were 1.07 times more likely to be obese and 4.32 times more likely to have elective cesarean section (C-section) delivery than those who engaged in moderate activity.ConclusionThe study found that physical activity during pregnancy has several beneficial effects on maternal prenatal health outcomes, including a reduced risk of obesity and C-section delivery, lower blood glucose levels, and improved mental health. Therefore, it is essential to adhere to the recommended guidelines for physical activity during pregnancy. Healthcare providers and policymakers in India should consider promoting physical activity as part of comprehensive routine prenatal care.